A novel syndrome of congenital sideroblastic anemia, B-cell immunodeficiency, periodic fevers, and developmental delay (SIFD) - Wiseman, Daniel H.; May, Alison; Jolles, Stephen; Connor, Philip; Powell, Colin; Heeney, Matthew M.; Giardina, Patricia J.; Klaassen, Robert J.; Chakraborty, Pranesh; Geraghty, Michael T.; Major-Cook, Nathalie; Kannengiesser, Caroline; et al. (Blood, 2013)
Congenital sideroblastic anemias (CSAs) are a heterogeneous group of inherited disorders identified by pathological erythroid precursors with perinuclear mitochondrial iron deposition in bone marrow. An international collaborative group of physicians and laboratory scientists collated clinical information on cases of CSA lacking known causative mutations, identifying a clinical subgroup of CSA associated with B immunodeficiency, periodic fevers, and development delay. Twelve cases from 10 families were identified. Median age at presentation was 2 months. Anemia at diagnosis was sideroblastic, typically severe (median hemoglobin, 7.1 g/dL) and markedly microcytic (median mean corpuscular volume, 62.0 fL). Clinical course involved recurrent febrile illness and gastrointestinal disturbance, lacking an infective cause. Investigation revealed B-cell lymphopenia (CD19+ range, 0.016-0.22 × 109/L) and panhypogammaglobulinemia in most cases. Children displayed developmental delay alongside variable neurodegeneration, seizures, cerebellar abnormalities, sensorineural deafness, and other multisystem features. Most required regular blood transfusion, iron chelation, and intravenous immunoglobulin replacement. Median survival was 48 months, with 7 deaths caused by cardiac or multiorgan failure. One child underwent bone marrow transplantation aged 9 months, with apparent cure of the hematologic and immunologic manifestations. We describe and define a novel CSA and B-cell immunodeficiency syndrome with additional features resembling a mitochondrial cytopathy. The molecular etiology is under investigation. • A novel clinical syndrome of CSA, B-cell immunodeficiency, periodic fevers, and developmental delay is described.• Bone marrow transplant resulted in complete and durable resolution of the hematologic and immunologic manifestations.